Comparative Evaluation of Analgesic, Anti-inflammatory and Antipyretic Effects of Synthetic Derivatives of Organoantimony (?) Ferocenyl Benzoate with Piroxicam - Akhtar, Muhammad Shoaib; Khan, Zulfiqar; Mushtaq, Muhammad Naveed; Akhtar, Muhammad Salman (Bangladesh Pharmaceutical Journal, 2016)
The current study was planned to evaluate comparative anti-inflammatory, analgesic and anti-pyretic activities of two newly synthesized organo-antimony (v) ferrocenyl benzoate derivatives with piroxicam. Anti-microbial activity of these compounds was also screened against two microorganisms. Analgesic effect of test compounds was evaluated by formalin-induced paw licking test in mice. The test compounds at 50 and 100 mg/kg b.w. doses exhibited significant (p<0.001) reduction of paw licking in treated mice comparable with standard drug piroxicam. Anti-inflammatory activity was assessed against carrageenan-induced paw oedema. The compound A produced anti-inflammatory effects comparable with standard piroxicam in dose dependent manner whereas compound B showed better effects than piroxicam at dose of 100 mg/kg body weight. To investigate anti-pyretic activity, fever was induced by administration of Brewers yeast in mice. Compound A showed highly significant inhibition of pyrexia (p<0.001) comparable to piroxicam after 3 hours while compound B (50 and 100 mg/kg) produced relatively lower anti-pyretic effect than standard drug. Antibacterial activity determined by disc diffusion method showed that compound B was relatively more effective than compound A against Staphylococcus aureus and Klebsiella pneumoniae. It is conceivable that both the tested compounds possessed anti-inflammatory, analgesic, anti-pyretic and anti-microbial effects even after the structural modification of parent compound. Bangladesh Pharmaceutical Journal 19(1): 15-24, 2016